“Wrapping the gastroduodenal artery stump” during pancreatoduodenectomy reduced the stump hemorrhage incidence after operation - Xu, Chang; Yan, Xinwei; Luo, Xiangji; Shen, Feng; Wu, Mengchao; Tan, Weifeng; Jiang, Xiaoqing (Chinese Journal of Cancer Research; Vol 26, No 3 (June 01, 2014): Chinese Journal of Cancer Research, 2014)
Objective: After pancreaticoduodenectomy (PD), the postoperative gastroduodenal artery stump (GDAS) hemorrhage is one of the most serious complications. The purpose of this study is to determine whether wrapping the GDAS during PD could decrease the postoperative GDAS hemorrhage incidence. Methods: A retrospective review involving 280 patients who underwent PD from 2005 to 2012 was performed. Wrapping the GDAS during PD was defined as “Wrapping the GDAS using the teres hepatis ligamentum during PD”. A total of 140 patients accepted the “wrapping” procedure (wrapping group). The other 140 patients didn’t apply the procedure (non-wrapping group). Age, sex, preoperative data, estimated intraoperative blood loss, postoperative complications, pathologic parameters and hospitalization time were compared between two groups. Results: There were no significant differences in patient characteristics between two groups. After wrapping, the incidence of postoperative GDAS bleeding decreased significantly (1/140 vs. 9/140, P=0.01). The rates of the other complications (such as intra-abdominal infection pancreatic fistula, billiary fistula, gastrointestinal bleeding, et al.) showed no significant differences. Conclusions: Wrapping the GDAS during PD significantly reduced the postoperative GDAS hemorrhage incidence. And the “wrapping” had no obvious influence on other complications.